2012
DOI: 10.1371/journal.pone.0042339
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Estrogen Receptor Alpha Is Upregulated during Subchronic Metabolic Stress and Inhibits Neuronal Cell Degeneration

Abstract: In addition to the classical nuclear estrogen receptor, the expression of non-nuclear estrogen receptors localized to the cell surface membrane (mER) has recently been demonstrated. Estrogen and its receptors have been implicated in the development or progression of numerous neurodegenerative disorders. Furthermore, the pathogenesis of these diseases has been associated with disturbances of two key cellular programs: apoptosis and autophagy. An excess of apoptosis or a defect in autophagy has been implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…A recent study demonstrated that activation of ERα by estradiol positively regulated the p-tau (Xiong et al, 2015). Differentiated SH-SY5Y cells contains a substantial level of estradiol receptors (Barbati et al, 2012;Grassi et al, 2013). Our findings showed that exposure to NE…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…A recent study demonstrated that activation of ERα by estradiol positively regulated the p-tau (Xiong et al, 2015). Differentiated SH-SY5Y cells contains a substantial level of estradiol receptors (Barbati et al, 2012;Grassi et al, 2013). Our findings showed that exposure to NE…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…26,27 Also in neurodegenerative diseases, gender differences in autophagy have been described. 28 In addition, almost all neurodegenerative diseases have higher incidence in females. 22 At certain prostate cancer cell types, androgen signaling plays a cardinal role in the choice between autophagy and apoptosis, former helping survival and metastasis formation, while latter delaying tumor growth.…”
Section: Applicationmentioning
confidence: 99%
“…Membrane-initiated estradiol signaling activates the novel protein kinase PKCθ, a critical step for inducing sexual receptivity [12,13] but it is still not clear whether other signaling pathways are activated. For example, other investigators have shown that membrane-initiated signaling and the insertion of ERα into the cell membrane involve the activation of the ERK pathway [14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%